Information and Communication Technology Adoption Models in Small and Medium Scale Enterprises: A Literature Review - Perera, M. H. D. N; Perera, M.P.S.R (Sri Lankan Journal of Entrepreneurship, 2021)
Information and Communication Technology (ICT) is regarded as an important aspect for both businesses and individuals alike. When it comes to businesses, the use of ICT is generally accepted to bring about enhanced performance and competitiveness through various means such as reduction of costs, an increase in efficiency and production. While knowledge of the use of ICT is necessary for businesses, it is equally important to understand the factors that would contribute to or affect such adoption by businesses as well. This study aims to analyse the several models that have been formulated over the years for the Adoption of ICT and summarize its applications, weaknesses, and strengths in explaining ICT Adoption. This literature review hopes to explore the most prominent theories: The Diffusion of Innovation Model, Technology, Organization and Environment (TOE) Framework, and the Iacovou et al. Model in an attempt to close the knowledge gap that exists concerning the Adoption of ICT by the Small and Medium Scale (SME) sector and its implications.
Keywords: : Information and Communication Technology, Small and Medium Scale Enterprises, Diffusion of Innovation